0201 A pilot of a taster workshop in simulation enhanced learning: Exposing local medical educators to teaching using simulation-based medical education. (2nd November 2015) - Gopal, Alan; Eccles, Sarah; Omer, Rasha; Purva, Makani
Abstract : Background: Teaching is a key component of clinical governance, and is encouraged throughout the medical community. 1 The Hull Institute of Learning and Simulation (HILS), 2 a primarily postgraduate institute, is committed to the provision of high-quality simulation-based medical education (SBME). Not only does it use simulation to provide medical education throughout HEY NHS trust, it also provides training in how to teach using SBME, with educational packages designed for all grades, from undergraduate to consultant level. Methodology: An innovative collaboration of student-led design and delivery with senior supervision enabled insight from both sides of the teaching partnership. 3 The 1 h workshop, held at the Hull York Medical School 9th Education Conference, was adapted from the successful postgraduate HILS Train-the-Trainers course 2 to suit an audience naïve to simulation. The workshop consists of an interactive plenary and high-fidelity simulation scenario. An audience-led debrief of the participant was facilitated to demonstrate the learning potential of SBME. 4 Pre and post-course questionnaires were used to assess educational value. Results: Attendees ranged from students to consultant-grade and included non-clinical faculty, all without formal training in SBME. Attendees demonstrated statistically and educationally significant changes in their attitudes towards SBME (scale 1 (wholly ineffective/un-enjoyable) to 5 (extremely useful/enjoyable)), considering it more effective (increase of 0.43/5, p = 0.02) and enjoyable (0.43/5, p = 0.03) to use, and indicated an increased likelihood to utilise SBME in future teaching. Quantitatively and qualitatively they found the workshop itself enjoyable, informative and useful, indicating they would like more access to SBME resources in future. Conclusion: SBME is an excellent tool when used appropriately, 4 and our results suggest there is scope to engage local medical educators in future in partnership in the pursuit of excellence in medical education. This pilot also demonstrated the strength of staff-student collaborations in the design and delivery of medical education. References: General Medical Council (GMC). Good medical practice 2013 . London: GMC, 2006 The Hull Institute of Learning and Simulation (HILS). Courses [Internet]. [cited 2014 Sept 1]. Available: http://www.hey.nhs.uk/hils/courses.htm/ Klazina Visser Katinka JAH, Prince Albert JJA, et al . Student participation in educational management and organization. Med Teach 1998;20(5):451–454 McGaghie WC, Siddall VJ, Mazmanian PE, et al . Chest. 2009;135 (3 Suppl): 62S–68S